Metta Bhavana meditation and resilience sunday school students’ at the Girikirti Buddhist temple - Wayan Rendi Setiawan; Taridi Taridi; Sidartha Adi Gautama (International Journal of Science and Applied Science: Conference Series, 2025)
This study aims to analyse the influence of Metta Bhavana meditation on the resilience of students at the Buddhist Sunday School of Wihara Girikirti. Metta Bhavana, as a form of mental cultivation in Buddhist teachings, is believed to foster boundless loving-kindness that strengthens both mental and emotional well-being. The research employed a quantitative approach using simple linear regression, involving proportionally selected students. Data were collected through questionnaires designed to measure the level of resilience and the intensity of meditation practice. The findings reveal that Metta Bhavana plays a significant role in shaping students’ mental and emotional resilience. Students who regularly engage in this meditation showed improvements in spiritual aspects, such as self-awareness and inner calm; emotional aspects, such as stress management and emotional stability; and social aspects, such as empathy and interpersonal communication skills. Nevertheless, resilience is also influenced by external factors, including family support, learning environment, and social interactions. These results offer important contributions to the development of Buddhist religious education curricula, particularly in non-formal settings such as Sunday Schools. Integrating Metta Bhavana into structured learning programmes, with the active involvement of teachers, parents, and the community, is considered an effective strategy for strengthening students' psychological resilience in facing life's challenges. Future research is recommended to explore mediating or moderating variables and to employ mixed-method approaches to gain a more comprehensive understanding of students' psychological and social dynamics.